Cellular and Molecular Responses to Mechanical Expansion of Tissue - Razzak, Muhammad Abdur; Hossain, Md. Sanower; Radzi, Zamri Bin; Yahya, Noor Azlin B.; Czernuszka, Jan; Rahman, Mohammad T. (Frontiers in Physiology, 2016)
The increased use of tissue expander in the past decades and its potential market values in near future give enough reasons to sum up the consequences of tissue expansion. Furthermore, the patients have the right to know underlying mechanisms of adaptation of inserted biomimetic, its bioinspired materials and probable complications. The mechanical strains during tissue expansion are related to several biological phenomena. Tissue remodelling during the expansion is highly regulated and depends on the signal transduction. Any alteration may lead to tumour formation, necrosis and/or apoptosis. In this review, stretch induced cell proliferation, apoptosis, the roles of growth factors, stretch induced ion channels, and roles of second messengers are organized. It is expected that readers from any background can understand and make a decision about tissue expansion.